Defining Human Rights in Times of Covid: Human Rights Discourse in the UK and Devolved Legislatures - Anne Cousson (Revue Française de Civilisation Britannique)
The British government’s reaction to the Covid-19 pandemic has meant wide-ranging restrictions imposed on people living in the UK with minimal parliamentary oversight. Thus, human rights and civil liberties were affected, as far as both individual freedoms and constitutional guarantees are concerned. However, given the urgency created by the health crisis and the controversial nature of human rights speech in the UK, using it to criticize the government’s measures was bound to be a politically charged choice. Through an analysis of parliamentary discourse in the main Covid-related debates both in the British Parliament and in the devolved legislatures, this article argues that human rights were not used as an expression of common values in a time of national crisis, but as a divisive rhetorical tool. Focusing thus on political discourse rather than on the effective effects of Covid restrictions on human rights allows us to identify ideological fault lines. Indeed, the analysis shows a highly differentiated definition of human rights between political parties on the one hand and between the different nations on the other.